(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the organization and development of fine arts as a science in Uzbekistan. The place of teaching fine arts in a comprehensive secondary school in the education of youth, the goals and objectives of science, people who contributed to the development of science, the importance of fine arts in human development, and methodological recommendations are given